(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to explore the possibility of preparing and analyzing financial statements according to the taxonomy classification developed using the eXtensible Business Reporting Language (XBRL) and its impact on measuring the continuity of private banks operating in Iraq. It also seeks to diversify the use of available electronic applications with artificial intelligence to predict the ability to continue, as well as to assess the capability of providing the necessary liquidity to prevent reaching a state of financial distress or failure that threatens banks. The research sample consisted of one of the major private banks for the years 2020-2021. The key findings indicate that the lack of implementation of XBRL in the banking sector leads to difficulties in making comparisons and evaluating banks due to the inconsistency in financial statement disclosures, as a result of not relying on the taxonomy classification that mandates preparers of financial statements to adhere to approved accounting disclosures and interpretations. The main recommendations of the researcher emphasize the necessity of adopting smart applications stemming from XBRL, which will contribute to quickly identifying weaknesses in banking liquidity, thereby practically threatening the bank’s ability to continue its operations and provide services